Experiences from Muhammadiyah on Practices of Multicultural Education: Analysis Through Bourdieu's Concept of Social Capital - Sri Roviana (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This article aims to answer the question of whether a multicultural perspective has been implemented in higher education. Muhammadiyah, an Islamic organization, has a strategic role in building and developing multicultural education in Indonesia. Ethnic, cultural, and religious diversity is critical for Muhammadiyah Education, so a multicultural perspective becomes the center of attention. Until now, the education practice organized by Muhammadiyah tries to practice a multicultural perspective so that it does not reject students from non-Muslim religions, diverse ethnicities, and varied cultures. All students are treated equally without being differentiated because they come from different religions and do not even have a Muhammadiyah background. This research is an analytical qualitative method with case studies approach. Therefore, teachers or lecturers, in providing knowledge and transferring values, need to understand clearly the diversity of students or students they face. Hence, a multicultural perspective becomes one of the requirements for lecturers or teachers to understand. This article used the perspective of social capital theory from Pierre Bourdieu to analyze the capital used in multicultural education at Muhammadiyah Universities, such as Universitas Ahmad Dahlan and Universitas Muhammadiyah Yogyakarta.